Quench simulation results for a 12-T twin-aperture dipole magnet. (June 2018) - Cheng, Da; Salmi, Tiina; Xu, Qingjin; Peng, Quanling; Wang, Chengtao; Wang, Yingzhe; Kong, Ershuai; Zhang, Kai
Highlights: An adiabatic analysis of the protection with only dump resistor by numerical computation. The multi-physics quench simulation with different protection methods. A four-fold asymmetric quench heater is developed. The estimate of heater performance by heater delay calculation. Abstract: A 12-T twin-aperture subscale dipole magnet is being developed for SPPC pre-study at the Institute of High Energy Physics (IHEP). The magnet is comprised of 6 double-pancake coils which include 2 Nb3 Sn coils and 4 NbTi coils. As the stored energy of the magnet is 0.452 MJ and the operation margin is only about 20% at 4.2 K, a quick and effective quench protection system is necessary during the test of this high field magnet. For the design of the quench protection system, attention was not only paid to the hotspot temperature and terminal voltage, but also the temperature gradient during the quench process due to the poor mechanical characteristics of the Nb3 Sn cables. With the adiabatic analysis, numerical simulation and the finite element simulation, an optimized protection method is adopted, which contains a dump resistor and quench heaters. In this paper, the results of adiabatic analysis and quench simulation, such as current decay, hot-spot temperature and terminal voltage are presented in details.